Some Mathematical and Physical Errors of Wald on General Relativity (Global Journal of Science Frontier Research, 2013)
In spite of including crucial errors, Wald's book has become a standard reference, in part, because the 1993 No-bel Prize Committee for physics made the same mist-akes. He also has circumvented some errors of Misner, Thorne and Wheeler, but he still fails to understand Einstein's equivalence principle. Moreover, he maintains the major common errors, the existence of dynamic and wave solutions for the Einstein equation, and thus also the claimed validity of linearization for weak gravity and the perturbation approach. Another problem is that he failed to see the invalidity of Einstein's covariance principle in physics. This is due to that in spite of his being additionally cautious, Wald was often not able to tell the difference between mathematics and physics. Although his main errors have been shown in the literature, some theorists may not have the mathematical background or the time to go though these.
Keywords: einstein’s equivalence principle; dynamic solutions; principle of causality; mathematica l analysis 0420-q; 0420cv